EVALUASI ATRIBUT KESEDERHANAAN, KETEPATAN WAKTU DAN STABILITAS PADA SURVEILANS KESEHATAN HAJI - Riva Noviyanti (The Indonesian Journal of Public Health, 2016)
Every year, the Indonesian pilgrims reached 200 thousand people and the health risks were still high. Hajj health surveillance are conducted to determine the progression of the disease in terms of place and time in pilgrims, and used for prevention efforts. The purpose of this research was to evaluate the attributes of surveilance performed by Dinkes Kota Surabaya in 2015. The research was done in Dinkes Kota Surabaya. This research was descriptive and its implementation using interview techniques using an instrument such as a questionnaire sheet. Respondents were a managing officer of health surveillance program Hajj in Dinkes Kota Surabaya and at Puskesmas. Results from this study is the evaluation of the attributes of surveillance shows that health Hajj surveillance systems in Dinkes Kota Surabaya in 2015 already meet the attributes of flexibility, timeliness, sensitivity, representativeness and acceptability. The evaluation of the attributes of surveillance is not fulfilled on health Hajj surveillance systems in Dinkes Kota Surabaya are attributes of simplicity, data quality and stability, while the positive predictive value can not be calculated. Advice that can be given are making plans a schedule for examining prospective pilgrims, monitoring the reporting and increasing the number of surveillance personnel.Keywords: evaluation, atribute of surveillance, health hajj surveillance